Profiles of systemic lupus erythematosus patients with co-existing sickle cell disease: a coincidence or true association? - Hakeem Babatunde Olaosebikan; Etseoghena Igebu; Adebukola Khairat Orolu; Gbenga Joshua Odunlami; Ilo Azizat Bamisebi; Akin Dada; Ebele Uche; Olufemi Adelowo (Rheumatology)
Introduction Systemic lupus erythematosus (SLE) and sickle cell disease (SCD) are distinct multisystemic diseases that commonly affect blacks. There are few reports of their co-existence in Western literature and a paucity of reports in Sub-Saharan Africa. Their co-existence is associated with diagnostic delay and treatment dilemmas. The aim is to describe the clinical, laboratory, and treatment profile of Nigerian lupus with sickle cell disease.